Integrated soil, water and agronomic management effects on crop productivity and selected soil properties in Western Ethiopia - Teklu Erkossa; Timothy O. Williams; Fanuel Laekemariam (International Soil and Water Conservation Research, 2018)
Land degradation is a major challenge limiting crop production in Ethiopia. Integrated soil and water conservation is widely applied as a means to reverse the trend and increase productivity. This study investigated the effects of such integrated approaches at two sites, Jeldu and Diga, in Western Ethiopia. A split plot design with physical soil and water conservation in the main plots and agronomic practices in the sub plots was employed. Maize (Zea mays L.) followed by groundnut (Arachis hypogaea L.) at Diga, and wheat (Triticum aestivum) followed by faba bean (Vicia faba L.) were the test crops. Surface soils were sampled before sowing and after the crop harvest, and analyzed for selected parameters. Soil moisture content during the growing period was also monitored. The use of soil bund increased soil moisture content, and significantly (P < 0.05) increased days to flowering and maturity, kernel weight and harvest index, grain yield of the test crops, with the exception of maize. The improved agronomic practices (intercropping, fertilization and row planting) significantly (P < 0.05) increased grain yield of all the test crops. The effect of the treatments on soil parameters may require longer time to be evident. Although the increase in crop yield due to soil bund and the improved agronomic practices is eminent, economic analysis is necessary before recommending the widespread use of the improved options. Keywords: Land degradation, Soil bund, Inter-cropping, Improved crop varieties, Crop-livestock systems